Honduras : Fourth Reviews Under the Stand-by Arrangement and the Arrangement Under the Standby Credit Facility, Requests for Augmentation of Access, Extension and Rephasing of the Arrangements, and Waivers of Nonobservance of Performance Criteria-Press Release; Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2021)
The protracted pandemic and two tropical storms have hit Honduras hard. Despite authorities' responses, these shocks continue to weigh on activity; reconstruction needs are high while the outlook remains uncertain. The authorities plan to rebuild a more climate-resilient economy, given Honduras' vulnerabilities to climate change. Presidential elections are scheduled for November 2021.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Honduras